Peran Komisi Penanggulangan AIDS Kota Semarang dalam Penyadaran Masyarakat Rentan HIV dan AIDS - Yosie Renda; Sulistyowati .; Dzunuwanus Ghulamanar (Journal of Politic and Government Studies, 2015)
Semarang is the most affected by HIV (Human Immunodeficiency Virus) and AIDS (Acquired Immuno Deficiency Syndrome) in Central Java Province. High-risk practices is the one of the affect factors to get exposed to HIV and AIDS. The local government has coped the case by establishing Semarang AIDS Prevention Commission. The commission was formed in 2010, whilst during 2010 to 2013 a significant increase of HIV and AIDS number has been found. The improvement is associated with the commission’s work performance since its early years, especially to prevent the society at risk to expose to HIV and AIDS. The research is to observe the role of Semarang AIDS Prevention Commission through out 2010 to 2013 over people who are at risk to get affected by HIV and AIDS, to find out the affect factors during those years, as well as to discover how the commission’s programs relate to the prevention of the prone society. Author uses qualitative method with descriptive approach to collect data by means of observation, interview and document studies. Research is conducted in Semarang AIDS Prevention Commission with supporting interview with the policy-holders and and the parties concerned. To overcome the transmission of HIV and AIDS in Semarang, Semarang AIDS Prevention Commission carry out programs to prevent the society at risk. Programs are delivered by the members and the working groups of the commission, funded by the Regional Government Budgets (APBD) through Health Department (Dinkes) and helped by Global Fund grants. The increasing number of HIV and AIDS when the commission’s first years after being established is a good result, it gives a hint that the commission has done the job well and better by finding more cases, however, member coordinations and funds are the most hampers to running the programs.Enforcement of member coordinations and availability of funds are the key to effective and maximum conduct in preventing sociey at risk to expose to HIV and AIDS. Key words : Semarang AIDS Prevention Commission, HIV – AIDS, society at risk